Identification procedures for the gifted at the Pagkakaisa Elementary Pilot School - Saladanan, Liberato Vidoya 1944- (College of Education, University of the Philippines Diliman, 1967)
The aim of the study was to research procedures employed in identifying the gifted pupils at the Pagkakaisa Elementary Pilot School with a view of seeking further improvements. The methods of research was chiefly documentary and was further supplemented by direct observation. The study concludes that for greater success in identification, use a combination, or if possible, all of the known procedures. There should likewise be continuous appraisal of children in general and of gifted children in particular.